G282(P) Gastrostomy prevalence in the paediatric population: a systematic review. (25th October 2020) - Lau, R; Kharma, N; Pardy, C; Kelly, V; Yardley, I
Abstract : Aim: It is known that the rate of gastrostomy insertion in the paediatric population is increasing. The prevalence of gastrostomies in the paediatric population has significant implications for health service provision, both for insertion and long-term management of the tubes. We sought to identify published literature describing the prevalence of gastrostomy tubes in the general paediatric population. Methods: A systematic review was performed using the keywords 'gastrostomy', 'paediatric', and 'prevalence' to search PubMed and Medline. The search was limited to 2008–2019. Duplicates and abstracts not containing the word 'gastrostomy' were excluded. The remaining abstracts were read. Full text versions of those relevant to the study were selected and the references scrutinised for any additional articles that were of interest to the study. Results: The initial search returned 3953 articles; 552 duplicates were excluded. The remaining 3401 articles were censored to those published in the last ten years (2008–2019), leaving 2060. 526 included the word 'gastrostomy', whose abstracts were read, leaving 15 papers focusing specifically on gastrostomy prevalence for which the full text was read. The references of these papers were scrutinised, yielding 1 additional publication, bringing our final count to 16. Of the 16 papers, only 8 were exclusively paediatric. Four of these were studies of population-wide period prevalence. Of these, three studied gastrostomy tube insertions (one solely PEG insertions), two report insertion rates across a population, but not the prevalence of indwelling gastrostomy tubes in that population. Only one study reported the prevalence of gastrostomy in a paediatric population. This found a rate of tube feeding at home of 83–92:100, 000 children/year, of which 60% were gastrostomy tubes (50–55 gastrostomies/100, 000 children/year). Conclusion: There is a significant volume of published literature describing the indications for, insertion techniques and complications of gastrostomy. However, literature relating to the prevalence of gastrostomy use in the paediatric population is scarce. Further studies are required reporting the prevalence of gastrostomies across a paediatric population, as this has significant resource implications and is of interest to policy makers, health care commissioners and providers.